Efektivitas Pembelajaran Berbasis STEM dalam Meningkatkan Kreativitas dan Keterampilan Berpikir Kritis Siswa SMP Negeri 1 Jombang - Azizah, Ainiyatul; Angelina, Nania Nova (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aims to examine the effectiveness of STEM-based learning (Science, Technology, Engineering, and Mathematics) in enhancing students' creativity and critical thinking skills at SMP Negeri 1 Jombang. The background of this research is rooted in the low level of student engagement in conventional learning processes, which tend to emphasize memorization rather than the development of higher-order thinking skills. The research method used was a quasi-experimental design with a pretest-posttest control group. The research sample consisted of two classes: an experimental class that implemented STEM-based learning and a control class that used conventional learning methods. Research instruments included a critical thinking test, creativity observation sheets, and student response questionnaires. Data analysis results showed a significant increase in students’ creativity and critical thinking scores in the experimental class compared to the control class. This improvement was confirmed through statistical testing using the t-test and normalized gain, which indicated a high level of effectiveness in the experimental group. Furthermore, the questionnaire results revealed that students responded positively to the STEM-based learning approach, finding it more engaging, challenging, and relevant to real-life contexts. Therefore, it can be concluded that STEM-based learning is effective in improving the creativity and critical thinking skills of junior high school students. These findings recommend the broader implementation of STEM learning models in the context of Indonesian lower secondary education